Kerjasama Indonesia Amerika di bidang Vaksinasi Hingga Peningkatan Neraca Perdagangan - Tasya Feronica Siregar; Sigit Tri Satya Sitepu; Tamaulina Br. Sembiring (PT. ALHAFI BERKAH INDONESIA, 2024)
Since the beginning of the COVID-19 pandemic, the world has faced challenges not only in the health sector but also in the economy. Indonesia and America, as two countries with great strategic and economic interests, have collaborated, especially in handling the pandemic through vaccine distribution and efforts to increase trade. The specific aim is to evaluate how this strategic cooperation encourages an increase in the trade balance between the two countries. The study results show that vaccination cooperation has facilitated increased health diplomacy which in turn has opened pathways for broader trade negotiations. The United States, as one of the largest vaccine producers, is the main partner in providing vaccines in Indonesia, which contributes to strengthening bilateral relations. This helps support Indonesia's economic recovery through stabilizing the health sector which has an impact on increasing trade activity. In turn, the trade balance between Indonesia and America has increased significantly, driven by exports and imports of health goods and main raw materials. Cooperation in the field of vaccination not only strengthens public health relations between Indonesia and America but also implies an increase in bilateral trade relations. This study emphasizes that international cooperation in the context of a crisis can be used as momentum to strengthen broader economic cooperation, creating a win-win situation for the countries involved. Further research could focus on the sustainability strategy of this kind of cooperation in the long term and its impact on global economic stability.